2014
DOI: 10.1002/ccr3.127
|View full text |Cite
|
Sign up to set email alerts
|

An interesting case of primary squamous cell carcinoma of the colon with synchronous metastatic adenocarcinoma

Abstract: Key Clinical MessageWe present a case of primary squamous cell carcinoma of the colon with synchronous metastatic adenocarcinoma. This case highlights the poor prognosis of these late presenting cancers. Furthermore, the unusual dual pathology raises questions about its potential etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Case two was initially clinically diagnosed as stage 4 SCC and received capecitabine, then radiation with carboplatin and paclitaxel, and lastly three cycles of 5-FU, oxaliplatin, and leucovorins, each with disease progression. Another unique comparison is that both of our patients were much younger than the average reported mean age of 53–60 [ 2 , 13 ].…”
Section: Discussionmentioning
confidence: 97%
“…Case two was initially clinically diagnosed as stage 4 SCC and received capecitabine, then radiation with carboplatin and paclitaxel, and lastly three cycles of 5-FU, oxaliplatin, and leucovorins, each with disease progression. Another unique comparison is that both of our patients were much younger than the average reported mean age of 53–60 [ 2 , 13 ].…”
Section: Discussionmentioning
confidence: 97%
“…Although the etiology and pathogenesis of SCC are unclear, there have been multiple possible hypotheses regarding the pathophysiology of the SCC. These theories propose that chronic inflammatory bowel disease, inflammation due to infection, mucosal injury, squamous cell differentiation by pluripotent stem cells, or radiation exposure can lead to squamous metaplasia [4,8,9]. Pre-existing adenomas or adenocarcinomas and associated HPV infection have been hypothesized to develop into SCC [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Frequently reported symptoms include rectal bleeding, abdominal pain, change in bowel habits, weight loss, and bowel obstruction [ 2 ]. In the literature review, we only found three cases describing sigmoid or splenic flexure perforation, but none with cecal perforation [ 7 - 9 ]. Given the unclear underlying mechanism of these malignancies and how infrequently they present, the following criteria have been proposed by Williams et al to diagnose SCC of the colon: (1) no evidence of a primary SCC elsewhere that could be a source of metastatic or direct extension to the bowel, (2) the affected segment of the bowel is not in continuity with a squamous lined fistula, (3) there is no continuity between the tumor and the anal squamous epithelium, and (4) confirmation of SCC by histological analysis [ 3 ].…”
Section: Discussionmentioning
confidence: 99%